Kinetic analysis of a complete poxvirus transcriptome reveals an immediate-early class of genes - Assarsson, Erika; Greenbaum, Jason A; Sundström, Magnus; Schaffer, Lana; Hammond, Jennifer A; Pasquetto, Valerie; Oseroff, Carla; Hendrickson, R Curtis; Lefkowitz, Elliot J; Tscharke, David C; Sidney, John; Grey, Howard M; et al. (Proceedings of the National Academy of Sciences - PNAS, 2008)
Vaccinia virus is the prototypic orthopoxvirus and was the vaccine used to eradicate smallpox, yet the expression profiles of many of its genes remain unknown. Using a genome tiling array approach, we simultaneously measured the expression levels of all 223 annotated vaccinia virus genes during infection and determined their kinetics. For 95% of these genes, significant transcript levels were detected. Most remarkably, classification of the genes by their expression profiles revealed 35 genes exhibiting immediate-early expression. Although a similar kinetic class has been described for other virus families, to our knowledge, this is the first demonstration of its existence in orthopoxviruses. Despite expression levels higher than for genes in the other three kinetic classes, the functions of more than half of these remain unknown. Additionally, genes within each kinetic class were spatially grouped together in the genome. This genome-wide picture of transcription alters our understanding of how orthopoxviruses regulate gene expression.